The third bullet [compact disc, unabridged] : a Bob Lee Swagger novel - Hunter, Stephen, 1946- (Hunter, Stephen, 1946- Bob Lee Swagger novel., 2012)
New York Times bestselling author Stephen Hunter is back with the biggest book of his career, in which his legendary Marine sniper hero Bob Lee Swagger probes the lingering mystery of John F. Kennedy's assassination and exposes the mastermind behind the third bullet. Why did the third bullet explode? The Warren Commission had no idea. The four thousand authors and investigators who followed remain clueless, but Bob Lee Swagger knows.